Analysis of Village-Owned Enterprises (BUMDes) Governance in Increasing Village Original Income in Denpasar City - Made Prastika Pramesti; Ni Putu Tirka Widanti; Nyoman Diah Utari Dewi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract This study aims to analyze the governance of Village-Owned Enterprises (BUMDes) in enhancing Village Original Revenue (PADes) in Denpasar City, with a case study on BUMDes Puspa Harum Sejahtera in Tegal Harum Village. The research employs a descriptive qualitative approach, using data collection techniques such as interviews, observations, and documentation. The findings reveal that governance principles such as transparency, accountability, and participation have been optimally implemented. BUMDes Puspa Harum Sejahtera has contributed significantly to the village’s revenue annually. However, challenges remain, including limited human resources and a lack of awareness in other villages regarding the importance of establishing BUMDes. Strengthening institutional capacity, providing human resource training, and enhancing collaboration with stakeholders are identified as key solutions to ensure the sustainability of effective BUMDes governance. Keywords: Governance, BUMDes, Village Original Revenue, Tegal Harum Village, Denpasar